Analyzing Sociolinguistic Aspects of Code-Switching Among Indians on Social Media Platforms - Nisa, Dr. Sarwat Un; Wani, Dr. Neelofar Hussain (Migration Letters, 2023)
The term code-switching is quite close to the concept of multilingualism, as it can be defined as the act of having a conversation in some language other than that of the individual’s mother tongue. The primary objective is to intertwine two elements: the widespread use of social media for communication and the practice of code-switching between English and Hindi languages, specifically within the context of WhatsApp. Employing a quantitative approach, data was systematically collected across India through a structured questionnaire employing a 5-Point Likert Type scale. The study reveals a prevalent occurrence of code-switching between English and Hindi on WhatsApp, emphasizing its connection to language comfort and fluency. The regression model, constructed from the data, underscores the influential role of comfortability and emotive expression in shaping the intention to continue code-switching. Users in India demonstrate a pronounced inclination toward code-switching, driven by the perception that employing a combination of both languages enhances emotive expression and facilitates better understanding among communication participants. This study contributes valuable insights into the dynamics of code-switching within the realm of social media communication, particularly on the widely used platform of WhatsApp.